Avocado Juice As a Non-Pharmacological Therapy In Addressing Adolescent Health Issues At Gpib Shalom, Depok City - Badria Laili; Retno Widowati; Vivi Silawati (Griya Eka Sejahtera, 2026)
Background: Adolescents undergo rapid physical, psychological, and intellectual growth and development, which can affect their health. Various health issues such as dysmenorrhea, anemia, acne, and digestive disorders are commonly experienced by adolescents, influenced by biological, psychological, social, and environmental factors, requiring appropriate attention and management. This study aimed to determine the effectiveness of avocado juice as a non-pharmacological therapy to address health issues among adolescent girls at GPIB Shalom in Depok City.Methods: The study used a quasi-experimental design with a one-group pre-test and post-test format. The study population consisted of 25 adolescent girls experiencing dysmenorrhea at GPIB Shalom in Depok City, selected using purposive sampling.Results: The univariate test results showed a decrease in the average dysmenorrhea pain from 4.28 to 2.56, an increase in hemoglobin levels from 9.816 g/dL to 10.700 g/dL, a reduction in skin health issues from 6.44 to 4.320, an improvement in skin moisture from 34.090 to 38.160, and a better bowel movement pattern from 2.320 to 3.64. The bivariate test results showed significant differences for all variables, with a p-value of 0.000 for dysmenorrhea pain (Z = -4.532), hemoglobin levels (t = -6.449), skin health issues (Z = -3.758), skin moisture (t = -8.839), and bowel movement patterns (Z = -4.562). This indicates that the administration of avocado juice has a positive effect on all tested variables.Conclusion: The conclusion of this study is that the consumption of avocado juice significantly reduces dysmenorrhea, increases hemoglobin levels, improves bowel movement patterns, maintains skin moisture, and reduces skin health issues in adolescent girls. The provision of avocado juice has the most significant impact on dysmenorrhea.